AN OPERATIONAL MODEL OF SEMIOTIC-BASED TRANSLATION: INTEGRATING PEIRCE-BARTHES IN BIDIRECTIONAL TRANSLATION OF THE HUNGER GAMES - Jepri Jepri (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2025)
Semiotic techniques have historically influenced translation theory; however, they primarily focus on analytical interpretation rather than providing operational direction in the translation process. This work presents an operational semiotic translation model that integrates Peirce’s sign typology with Barthes’ multi-layered meaning theory to address this gap. The study employs a qualitative descriptive design and utilizes a six-stage translation procedure: sign mapping, denotative transfer, connotative adjustment, myth preservation, semiotic reformulation, and bidirectional testing, applied to selected textual units from The Hunger Games and its English-Indonesian translations. The results indicate that the proposed approach methodically directs translator decision-making and improves the retention of semiotic function, especially symbolic and ideological meaning, across translation orientations. Bidirectional testing elucidates persistent patterns of semiotic loss and gain, alongside differing levels of ideological stability and change, suggesting that translation functions as a process of systematic semiotic transformation rather than mere equivalence transfer. The study advances theory by redefining semiotics as a translation method rather than an interpretive framework, enhances methodology by presenting a clear and replicable operational model, and offers practical use through a structured framework relevant to translation practice and instruction. This study expands the operational reach of semiotic translation studies by integrating semiotic theory, methodological procedures, and translational applications.